2006
DOI: 10.1002/path.1943
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of VEGF-C and VEGFR-3 in glioblastomas and haemangioblastomas

Abstract: Primary human brain tumours account for approximately 2% of all cancers. High levels of expression of vascular endothelial growth factor-A (VEGF-A), a potent angiogenic factor, are linked to poor prognosis. In contrast, the potential role in human brain tumour biology of newer VEGF family members, VEGF-C and VEGF-D, both of which are lymphangiogenic factors, is poorly understood. In the present study, the expression of all VEGFs (VEGF-A, -B, -C, and -D) and their receptors (VEGFR-1, -2, and -3) has been assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 41 publications
(40 reference statements)
4
46
1
Order By: Relevance
“…For example, Hoshida and colleagues (15) showed, using intravital microscopy, that VEGF-C increases invasion of tumor cells into draining lymphatic vessels. Furthermore, several recent studies have shown that both VEGFR-3 and VEGF-C are expressed by metastatic tumor cells (16)(17)(18)(19)(20)(21), suggesting autocrine stimulation mechanisms that may include tumor cell proliferation (19,22) and invasiveness (21,23,24) of tumor cells, directly or indirectly by increasing flow into hyperplastic peritumoral lymphatics (11,15). These findings suggest that VEGF-C may act in multiple ways to promote lymphatic invasion.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…For example, Hoshida and colleagues (15) showed, using intravital microscopy, that VEGF-C increases invasion of tumor cells into draining lymphatic vessels. Furthermore, several recent studies have shown that both VEGFR-3 and VEGF-C are expressed by metastatic tumor cells (16)(17)(18)(19)(20)(21), suggesting autocrine stimulation mechanisms that may include tumor cell proliferation (19,22) and invasiveness (21,23,24) of tumor cells, directly or indirectly by increasing flow into hyperplastic peritumoral lymphatics (11,15). These findings suggest that VEGF-C may act in multiple ways to promote lymphatic invasion.…”
Section: Introductionmentioning
confidence: 83%
“…We next examined whether VEGF-C had autocrine effects on the tumor cells because others have reported correlations between tumor VEGFR-3 and metastasis (17,18,20,23,40), although expression of VEGFR-3 in some tumor cell lines has been debated. We saw no expression in any cell line when cultured in two-dimensional conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF-C can also attract macrophages [124] that can alter the tumor microenvironment to promote invasion. Furthermore, some tumor cells also express VEGFR-3 and thus may benefit from autocrine signaling of VEGF-C or -D [121,[125][126][127][128][129]. Such autocrine signaling could help tumor cells home to lymphatics by guiding them in the direction of flow [42].…”
Section: Chronic Graft Rejectionmentioning
confidence: 99%
“…For example, gliomas do not induce lymphangiogenesis (48), and microglia associated with gliomas are particularly active at secreting TGF-␤ that contributes to invasiveness (49). Gliomas are also comprised of different stromal elements than peripheral tumors.…”
mentioning
confidence: 99%